超臨界二氧化碳環境下對套管水泥力學與物化性質之影響 - 江健豪; Chiang, Chien-Hao (2012)
以人為方式將二氧化碳長期封存於地質構造，為目前各界廣為接受的二氧化碳封存技術之一。台灣地區經評估後選定陸上封閉油氣構造為較佳之二氧化碳封存場址。但注入之二氧化碳與地層水反應形成之碳酸(H2CO3)，將對井孔的套管水泥產生碳酸化反應。隨時間增加造成水泥材料之力學性質降低，膠結成分破壞，孔隙率與滲透率增加，進而可能造成二氧化碳藉由受碳酸化後無封固能力之套管水泥洩漏。 本研究模擬四種配比之套管水泥於井底環境(70℃、20MPa)兩種二氧化碳封存狀態下(超臨界狀態、溶於地層水狀態)，分四個反應時間點(0、7、14、28天)，對其力學與物化性質變化進行探討。本研究結果發現添加飛灰、矽粉與重晶石，可使套管水泥於反應期間產生緻密層，以減緩外部碳酸持續往內層侵蝕。API G級水泥+矽粉與重晶石有較佳之力學性質維持，因此有較佳之防止水泥碳酸化而崩解之能力。 The long-term anthropogenic CO2 storage in the geological formations is one of the widely accepted CO2 storage techniques In Taiwan the ideal CO2 storage site is assessed to be the closed oil and gas reservoirs CO2 being injected into the geological formations with groundwater will become the carbonic acid (H2CO3) and it will carbonize the well cement of the wellbore When the reaction time increases the mechanical properties of the well cement will generally decrease and the porosity and permeability of the well cement will generally increase The carbonization is likely to have an adverse effect on the well cement This paper attempts to study the well cement with additives in the simulated environment under the supercritical CO2 (70℃ 20MPa) and the storage condition (CO2 with or without saturated brine) The evolutions of the mechanical physical and chemical properties were studied in four different periods (0 7 14 28 days) This study finds that the well cements with fly ash silica flour and barite produce dense layer during the reaction It can resist the continuous erosion inside of the cement by carbonic acid This study also finds that the mechanical properties of API G well cement with silica flour and barite have higher values than those of other well cements Therefore API G well cement with silica flour and barite has the best mechanical capability of resisting carbonization and degradation